JAK Inhibitors in the Treatment of Psoriasis and Psoriatic Arthritis and the Risk of Skin Malignancies: a Review of Current Evidence - Kacprzyk, Marta; Masajada, Magdalena; Kulbat, Aleksandra; Richter, Karolina; Brzewski, Paweł; Wysocki, Wojciech M. (Dermatology Review/Przegląd Dermatologiczny, 2025)
Psoriasis and psoriatic arthritis are chronic immune-mediated disorders associated with substantially impaired quality of life and comorbidities. Janus kinase (JAK) inhibitors have recently emerged as highly efficient therapeutic agents for the treatment of various inflammatory and hematologic diseases. Nevertheless, there are some concerns about potentially increased risks of infections and therapy-induced malignancies associated with utilization of JAK inhibitors. In this study, we review the current knowledge about the role of particular components of the JAK/STAT pathway in the carcinogenesis and explore the evidence on the safety of JAK inhibitors in relation to the risk of melanoma and non-melanoma skin cancer in patients with psoriasis and psoriatic arthritis.